Participation Costs, Trend Chasing, and Volatility of Stock Prices - Orosel, Gerhard O. (Review of Financial Studies, 1998)
We analyze an overlapping generations model with fixed costs of stock market participation. Participation in the stock market is determined endogenously and covaries positively with preceding innovations in dividends. The equilibrium share price is positively related to market participation of the same period and to information about future dividends. There is "rational trend chasing" in the sense that, although all agents are rational, market participation rises after an increase of the share price and falls after a decrease. Finally, we show that the endogenous fluctuations of market participation lead to increased volatility of the share price.